Un caso de queratoma en el casco de un caballo - Manso Díaz, G.; Rubio Guerri, C.; Sánchez Maldonado, B. (Revista Complutense de Ciencias Veterinarias, 2008)
Keratomas are uncommon benign neoplasms of the horse hoof with epithelial origin, which are developed from keratin-producing squamous cells of the hoof wall. Normally these processes are related to a previous history of intermittent lameness. Clinical, macroscopic and histopathologic features of a keratoma in the hoof of a horse with a clinical history of chronic lameness are described in this paper. The animal showed a deformity of the hoof frog due to the presence of a mass located at the junction of the coronary band with the white line. A neoplasic proliferation was observed at the histopathologic examination, consisting of epithelial cells and several layers of keratin.
Keywords: Keratoma; Hoof; Horse